First factor (x square -36), the answer will be (x+6)(x-6).
Second, cancel the x .
6x/ (x+6)(x-6)
4x/(6)(-6)
4x/-36
Answer:
6
reduce the expression and if possible do that by cancelling the common factors :)
It depend on where you are working at that isn't a specific question
Answer:
-6x+31/3
Step-by-step explanation:
Answer:
50 =x
Step-by-step explanation:
The two angles are vertical angles, so they are equal
2 (x+10) = 3x-30
Distribute the 2
2x+20 = 3x-30
Subtract 2x from each side
2x-2x+20 = 3x-2x-30
20 = x-30
Add 30 to each side
20+30 = x-30+30
50 =x